2002
DOI: 10.1063/1.1521569
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics and magnetic properties of chemically synthesized CoPt nanoparticles

Abstract: Co x Pt 100−x nanoparticles with dimensions from approximately 2 to 5 nm were synthesized using the reverse micelle method. High-resolution electron microscopy revealed single- and poly-crystalline nanoparticle structures. Twin boundary is a common feature in the polycrystals. As-grown nanoparticles did not show any coercivity at room temperature. However, the nanoparticles became ferromagnetic after annealing at 550 °C for 4 h. Face-centered-cubic to face-centered-tetragonal phase transformation of the nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 5 publications
1
51
0
Order By: Relevance
“…49 This change in the particle magnetic properties was essentially explained by the facecentered-cubic to face-centered-tetragonal phase transition occurring at annealing temperatures above 820 K. Nevertheless, the authors were not able to exclude particle coalescence as a main cause of the observed increase of the particle blocking temperature. Conversely, our MOKE measurements bear information, which can be used to exclude particle coalescence.…”
Section: Annealing Of Copt Nanocrystalsmentioning
confidence: 84%
“…49 This change in the particle magnetic properties was essentially explained by the facecentered-cubic to face-centered-tetragonal phase transition occurring at annealing temperatures above 820 K. Nevertheless, the authors were not able to exclude particle coalescence as a main cause of the observed increase of the particle blocking temperature. Conversely, our MOKE measurements bear information, which can be used to exclude particle coalescence.…”
Section: Annealing Of Copt Nanocrystalsmentioning
confidence: 84%
“…[26±31] The synthesis of CoPt nanoparticles using surfactant-based templating has been successful in producing monodisperse particles that can be ordered into two-dimensional (2D) arrays. These synthetic approaches include reducing metal-organic precursors with reductants such as borohydride and diols, [26,32,33] redox transmetallation reactions [34] using reverse micelles, [35] and microemulsion techniques. [36] Another promising approach is to use biomacromolecules as templates for directed fabrication of metallic nanophases.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies on the chemical synthesis and postannealing of FePt nanoparticle systems have been reported during the past several years [4][5][6][7][8][9]. It is well known that as-synthesized FePt nanoparticles take a disordered facecentred cubic (fcc) structure which has low magnetocrystalline anisotropy.…”
Section: Introductionmentioning
confidence: 99%